A description of premature and ex-premature infants admitted to a Paediatric Intensive Care Unit in the first six months of life - Mathew, Grace (Department of Paediatrics and Child Health, 2019)
Background: Prematurity is a major risk factor for morbidity and mortality in children. Rehospitalisation with paediatric intensive care unit (PICU) admission constitutes significant morbidity. There is a paucity of literature regarding rehospitalisations of premature infants in South Africa. Objective: To describe the outcomes, clinical course and characteristics of premature infants admitted to a South African PICU, and to identify any predictors of mortality. Methods: This prospective observational study analysed unplanned PICU admissions of premature and ex-premature infants in the first six months of life, over a six-month period. The primary and secondary outcomes were mortality and length of PICU stay, respectively. Data were analysed using standard descriptive and inferential statistics. Results: 29 infants (65% male; median (IQR) birth weight (BW) and gestational age (GA) 1715 (1130 - 2340) g and 32 (29 - 34) weeks respectively) in 33 admissions were included. Five (17.2%) infants died in PICU. Apnoea (39.4%), respiratory failure (24.2%) and shock (24.2%) were the commonest reasons for PICU admission, secondary to pneumonia (33.3%), sepsis (27.3%) and meningitis (12.1%). 72.4% of infants were mechanically ventilated and 48.3% received blood transfusions. Higher revised Paediatric Risk of Mortality (PIM2) score (p = 0.03), inotrope use (p < 0.0001), longer duration of mechanical ventilation (p = 0.03), and cardiac arrest in PICU (p < 0.0001) were associated with mortality on univariate analysis with no independent predictors of mortality. Conclusion: Infections leading to apnoea, respiratory failure and shock are common indications for PICU readmission in premature infants. Mechanical ventilation and blood transfusion were frequently required.